Quantifying inter-segmental coordination during the instep soccer kicks - Li, Y.; Alexander, M.; Glazebrook, C.; Leiter, J. (International Journal of Exercise Science, 2016)
In order to generate a high ball speed in soccer, the inter-segmental coordination of the kicking leg is critical. The purpose of this study was to quantify the coordination between the thigh and shank movement in the sagittal plane during instep kicks. Eleven female soccer players were video recorded using a high-speed (80 Hz) video camera during penalty kicks. Hip, knee and ankle joint centers of the right leg were digitized, and the movement was analyzed using Dartfish TeamPro (6.0). The thigh and shank segment angles were generated, and the coordination was quantified using the cross-correlation and the vector coding method. Four coordination patterns were defined based on coupling angles: in-phase, anti-phase, thigh-phase and shank-phase. The time spent in each coordination pattern was analyzed. The cross-correlation coefficient was positive for all the participants, indicating that the two segments rotated with similar patterns. Based on the vector coding method, we observed dominant coordination patterns of shank-phase and in-phase during the backswing and forward swing phase, respectively. We hope the outcomes of our study could provide a better understanding of soccer kicking coordination and benefit training young soccer players. Future studies may use the methodology and outcomes in the present study to investigate the coordination of different levels of players to better understand the process of skill acquisition.